Effect of the non-ionic surfactant Poloxamer 188 on passive permeability of poorly soluble drugs across Caco-2 cell monolayers - Fischer, Sarah Maud; Brandl, Martin; Fricker, Gert (European journal of pharmaceutics and biopharmaceutics, 2011)
Drug permeability of the model drugs ketoprofen and nadolol across Caco-2 cell monolayers was determined in the absence and presence of the non-ionic surfactant Poloxamer 188 (Pluronic® F68, P-188). Stringent controls confirmed that P-188 in concentrations up to 50mg/ml did not adversely affect cell viability or monolayer integrity. Equilibrium experiments confirmed that the drugs were merely passively transported. Caco-2 permeability of both drugs was found to be decreased by the surfactant in a concentration-dependent manner. Ultrafiltration revealed that both drugs were associated with surfactant micelles. The systematic investigation of micellization on passive absorption showed that association of drugs with P-188 micelles appears to depress their passive permeability under conditions where other transport mechanisms can be neglected.
Online verfügbar 28 April 2011
Gesehen am 16.01.2023